Isolation, Expansion, Differentiation and Growth Kinetics Essay in Mesenchymal Stem Cells Culture from the Bone Marrow of Collared Peccaries (Tayassu tajacu) - Neto, Napoleão Martins Argôlo; Feitosa, Matheus Levi Tajra; Sousa, Simony Silva; Fernandes, Paulo Brandão; Pessoa, Gérson Tavares; Bezerra, Dayseanny de Oliveira; Almeida, Hatawa Melo de; Carvalho, Yulla Klinger Pereira de; Rocha, Andressa Rego da; Silva, Laís Meireles Costa; et al. (Acta Scientiae Veterinariae, 2016)
Background: There are few studies on stem cell isolation in wild animals that provide isolation and culture protocols of these cells in vitro. Among the wild species studied, we present the collared peccary (Tayassu tajacu) as a model with potential to obtain and use MSC in preclinical studies. These animals are phylogenetically close to the domestic pig, popularly known as peccaries and found naturally in South America, Central America and the South of the United States. The aim of the present study was to establish a protocol for the isolation, in vitro cell expansion, differentiation and assessment of the stromal MSC growth curve before and after thawing. Materials, Methods & Results: Mesenchymal stem cells (MSC) from collared peccary bone marrow (Tayassu tajacu) were isolated and expanded by centrifuge in Ficoll® solution and cultured in DMEM® High Glucose medium. The culture was assessed by assays of colony forming units CFU-F and growth curve by saturation (GCS). Cultures in the third passage, with 70% confluence, were replicated at 105 cells/mL concentration in the culture media to induce osteogenic cell differentiation and adipogenic cell differentiation, respectively. The MSC were frozen in nitrogen for 40 days, thawed and re-assessed for cell viability and GCS. Discussion: The bone marrow collected presented high mononuclear cellularity, with a mean variability of 94.5% and 60.83 ± 4.27 UFC were identified in the samples and cells with fibroblast-like-cell morphology were observed. When they were expanded, the mean cell viability was 95%, the mean cell concentration obtained was 233.31 ± 20.04 cells per 25cm2 bottle and the culture reached the growth plateau in GCS between the 13th and 16th day. The osteoblastic cell differentiation assay showed after 18 days, morphology similar to osteoblasts, with irregular cytoplasm limits, cell prolongation formation and flattened appearance. After staining with Alizarin Red, the nucleus presented a wine red coloring and the cytoplasm, more basophilic and well-defined, with calcium deposits inside the cells. The cultures submitted to adipogenic differentiation were large, hexagonal, irregular and presented birrefringent cytoplasm granules after the third week of culture. When stained with Oil Red it was observed that the cytoplasm granules were scattered small fat vacuoles and stained maroon. The viability after thawing was 78% and the mean cell concentration obtained in GCS was 199.71 ± 14.72 cells per 25 cm2 bottle. The curves reached the saturation plateau early, on the eighth day of observation. From then onwards the cultures entered became exhausted and the cell concentration of the samples decreased progressively until minimum values. These results showed the presence of a well-defined MSC population in the collared peccary bone marrow with a high rate of replication in vitro and potential for differentiation confirmed by the adipogenic and osteogenic lines. The cryopreservation technique adopted presented satisfactory results, but indicated a significant cell stress after thawing that justifies investigation of the apoptosis rates induced post thawing in the species. Furthermore, the bone marrow collection did not harm the animals and the facility of stromal MSC isolation and culture qualifies the collared peccary as a viable alternative model to obtain MSC and for studies in the area of cell therapy.